The biocompatibility of a ginger-containing herbal toothpaste on developing zebrafish embryos - ALTURFAN, EBRU IŞIK (My University, 2023)
The biocompatibility of toothpaste in an oral cavity should be approved by clinical trials. Nowadays, herbal toothpaste is increasing in popularity due to its natural ingredients. Being genetically similar to humans, zebrafish are used in potential toxicity testing. The zebrafish embryotoxicity test is a fast and straightforward method to study chemical toxicity during embryogenesis. Objective: This study aimed to evaluate if there was any biocompatibility of the toothpaste on zebrafish embryos. Methods: Adult AB strain zebrafish were used according to Institutional Animal Care and Use Committee protocols. Normally dividing, spherical embryos were exposed to herbal toothpaste with ginger (Gumgumix, Turkey) (50 mg/L) and conventional toothpaste (Signal, Expert Protection, Bulgaria) (50 mg/L) in well plates containing 20 embryos, having four replicates. Developmental effects, mortality, and hatching rates were evaluated for 72h. Results: Zebrafish embryos exposed to conventional toothpaste had a higher mortality rate than those exposed to herbal toothpaste; they hatched later and delayed in development. There was no difference between herbal toothpaste and the control group regarding mortality and hatching rates (p > 0.005). Conclusion: The herbal toothpaste showed higher biocompatibility on zebrafish embryos compared to the conventional toothpaste under the condition of this study
Keywords: Diş Hekimliği; Yaşam Bilimleri; Biyokimya; Sağlık Bilimleri; Temel Bilimler; Dentistry; Life Sciences; Biochemistry; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Klinik Tıp; Doğa Bilimleri Genel; Biyoloji ve Biyokimya; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; ÇOK DİSİPLİNLİ BİLİMLER; BİYOKİMYASAL ARAŞTIRMA YÖNTEMLERİ; Clinical Medicine (MED); Natural Sciences (SCI); Life Sciences (LIFE); CLINICAL MEDICINE; NATURAL SCIENCES, GENERAL; BIOLOGY & BIOCHEMISTRY; DENTISTRY, ORAL SURGERY & MEDICINE; MULTIDISCIPLINARY SCIENCES; BIOCHEMICAL RESEARCH METHODS; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Multidisipliner; Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Multidisciplinary; development; embryo; toothpaste; toxicity; zebrafish